Mineralogical and Geochemical Study on the Yaojiazhuang Ultrapotassic Complex, North China Craton: Constraints on the Magmatic Differentiation Processes and Genesis of Apatite Ores - Pan, Ronghao; Hou, Tong; Zhang, Zhaochong (Frontiers in Earth Science, 2020)
The differentiation process of ultrapotassic magmas is enigmatic and poorly understood. The Yaojiazhuang ultrapotassic complex is concentrically zoned by late-intruded syenite in the core and early emplaced clinopyroxenite in the periphery, combining a “bi-modal” lithology. Spatially, apatite and iron oxide-apatite (IOA) ores, glimmerite and pseudoleucite occur in the upper part of clinopyroxenite. The syenite and clinopyroxenite are composed of variable amounts of clinopyroxenite, biotite, K-feldspar, magnetite, apatite with minor analcite, titanite, and primary calcite. The pseudoleucite clinopyroxenite contains mainly clinopyroxene, biotite and garnet in the matrix, and nepheline–K-feldspar intergrowth with muscovite and minor celestine in the leucite pseudomorph. Geochemically, rocks of the Yaojiazhuang complex are significantly enriched in potassium (K), light rare earth elements (LREE), and large ion lithophile elements (LILE). Crustal contamination by Archean tonalite–trondhjemite–granodiorite (TTG) gneisses basement may play an important role to convert the syenitic melts from silica-undersaturation to saturation. Fractionation crystallization is supported by the mineral crystallization sequence to explain the bimodal lithologies instead of silicate liquid immiscibility. During the magmatic evolution, decompression, fractionation of volatile-poor clinopyroxene and the enhancement by CO2 may result in the exsolution of an aqueous fluid. The late-stage interactions between existing minerals and magmatic fluids in the crystal mush could be a key process in the generation of both leucite pseudomorphs and apatite/IOA ores.